Paravertebral cervical block for osteosynthesis of humeral fracture in foal - Miyashiro, Vitor Yuji [UNESP]; Patto Dos Santos, Paulo Sérgio [UNESP]; De Almeida Lucas, Flávia [UNESP]; De Rezende Eugênio, Flávia [UNESP]; Peiró, Juliana Regina [UNESP]; Denadai, Daniela Scantamburlo [UNESP] (Universidade Estadual de Londrina, 2019)
A modified cervical paravertebral block of the brachial plexus was performed with the aid of a nerve stimulator for osteosynthesis with four intramedullary pins in a 5-month-old colt weighing 180 kg diagnosed with a closed, complete, and oblique humerus fracture. Xylazine 2% (0.5 mg kg-1 IV) was administered as the pre-anesthetic medication. Anesthesia was induced with ketamine 10% (2 mg kg-1 IV) and midazolam 0.5% (5 mg kg-1 IV) and maintained with isoflurane. The animal was on mechanical ventilation. The nerve block was induced with administration of ropivacaine 0.75% in the ventral branches of C6 (intervertebral space C5-C6) and C7 (intervertebral space C6-C7) and in the branches of C8 and T1 at their convergence at the cranial margin of the first rib. During the 130-min duration of the surgery, no analgesic rescue was required. In conclusion, this blockade can be performed safely and promotes numbness of the humeral and olecranon regions.
Keywords: Equine; Locoregional anesthesia; Nerve stimulator